IMPLEMENTATION OF ROAD AND DRAINAGE INFRASTRUCTURE DEVELOPMENT BY THE PUBLIC WORKS DEPARTMENT OF SIMALUNGUN REGENCY - Feby Milanie; Ruri Prihatini Lubis; Mhd. Ali Damanik; Anton Sahala Tua Banjarnahor (Bulletin of Engineering Science, Technology and Industry, 2026)
Road and drainage infrastructure development is an important component in supporting community mobility, economic growth, and environmental sustainability. Simalungun Regency as a region with extensive road network coverage still faces various problems, such as high levels of road damage and suboptimal drainage system function. This study aims to analyze the implementation of road and drainage infrastructure development carried out by the Simalungun Regency Public Works Department, by reviewing factors that influence the effectiveness of its implementation, the level of development integration, and the role of community participation based on the theory of Success Factors in Managing Wastewater Infrastructure through Community Participation . The research method used is a descriptive qualitative approach with data collection techniques through documentation studies, observations, and interviews. The results of the study indicate that the implementation of road and drainage infrastructure development has been carried out in accordance with regional planning, but its effectiveness has not been optimal. Budget limitations, human resource capacity, weak supervision, and low community participation are the main factors inhibiting the success of development. In addition, the integration between road development and the drainage system is still low, thus affecting the sustainability of infrastructure. Therefore, it is necessary to strengthen integrated development governance, increase community participation, and optimize supervision and funding so that road and drainage infrastructure development can be sustainable and provide long-term benefits for the people of Simalungun Regency.